2018
DOI: 10.1021/acsearthspacechem.8b00039
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Hydrocarbons with Clays under Reservoir Conditions: In Situ Infrared and Nuclear Magnetic Resonance Spectroscopy and X-ray Diffraction for Expandable Clays with Variably Wet Supercritical Methane

Abstract: The results from novel in situ high-pressure nuclear magnetic resonance (NMR) spectroscopy, infrared (IR) spectroscopy, and X-ray diffraction (XRD) investigation of the interaction of the smectite hectorite with variably wet supercritical methane (scCH4) at 90 bar and 323 K (hydrostatic conditions equivalent to ∼1 km depth) show that CH4 occurs in the clay interlayers, in pores external to the individual clay particles, and as bulk fluid. The occupancy of each environment depends on the relative humidity (RH) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
90
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(110 citation statements)
references
References 55 publications
17
90
3
Order By: Relevance
“…This conclusion is consistent with the incorporation of CH 4 into the interlayer galleries of expandable clays occurring by a passive, space filling mechanism with basal spacings similar to 7.5 Å. 39 Increasing CO 2 and CH 4 incorporation with increasing pore thickness also greatly effects the coordination of the Na + ions to the pore surfaces ( Fig. 3).…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…This conclusion is consistent with the incorporation of CH 4 into the interlayer galleries of expandable clays occurring by a passive, space filling mechanism with basal spacings similar to 7.5 Å. 39 Increasing CO 2 and CH 4 incorporation with increasing pore thickness also greatly effects the coordination of the Na + ions to the pore surfaces ( Fig. 3).…”
Section: Resultssupporting
confidence: 82%
“…These results are in good agreement with recent experimental and simulation studies that show that the basal spacing required for CO 2 intercalation in the interlayer galleries of smectite clays is less than for CH 4 due to steric effects. 6,31,32,38,39 At a pore thicknesses of 7.5 Å some CH 4 enters the pore, and the CO 2 /CH 4 ratio decreases rapidly with increasing pore thickness up to 33.0 Å ( Fig. 2a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Computational studies have shown that reducing the structural charge on the clay enhances CO2 intercalation, 37 and this may also contribute to intercalation of other hydrophobic species. As illustrated by recent experimental studies, the composition of the external fluid phase strongly affects the intercalation, with high H2O activities suppressing CO2 intercalation 21,[28][29][30][31]43 and presumably that of other hydrophobic species. It also seems likely that even with Fsubstitution, small linear and planar molecules should be more easily incorporated than large ones with complex molecular structures.…”
Section: Discussionmentioning
confidence: 96%
“…The model with 53% Fsubstitution has a composition similar to the natural San Bernardino hectorite (Clay Mineral Society SHCa-1) used in many spectroscopic studies by our group and others, which has 55% Fsubstitution. 21,42,43 Individual Fions occur in two different structural environments in the simulation models: (i) coordinated to 3 Mg octahedra and (ii) coordinated to 2 Mg and 1 Li octahedra. The ratio of these two sites used in the simulations is 60:40 in accordance with experimental 19 F NMR results for the natural San Bernardino sample.…”
Section: Methodsmentioning
confidence: 99%